Analisis statistik keterpakaian database online Science Direct (Januari- Juni 2018) dalam mengambil kebijakan pengadaan bahan pustaka elektronik pada Perpustakaan Universitas Islam Indonesia - Mestika Dewi (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2019)
The aim of the study was to look at the price of e-journals and e-books, the average cost per access and use of content in accordance with the original price of e-journals and e-books in taking the Library Material Procurement Policy specifically in subscribing to the direct science online database. The approach used in this study is descriptive. The object of this study is the statistics on the use of e-journals and e-books on ScienDirect at the Indonesian Islamic University Library (January-June 2018). To analyze the average cost per article, the average cost per use, and the use of appropriate content using e-book download statistics, e-journal search, division journal search, division journal download, Full-Text journal compilation and subscription costs. ScienceDirect. There are 5 benchmarks and analyzed using the three metric formula by Hahn and Faulkner. The results of data analysis show that subscribing to ScienceDirect greatly benefits the Indonesian Islamic University Library judging from the use of information sources in the digital format provided by ScienceDirect causing the price of articles and access costs to be far cheaper than not subscribing to ScienceDirect.